1978
DOI: 10.1037/0012-1649.14.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distinctive features on recognition of incomplete pictures.

Abstract: Two experiments were conducted to determine the effects of distinctive features on recognition of incomplete pictures. Two sets of fragmented picture stimuli were designed: Set A preserved 75% and Set B preserved 25% of the distinctive features of the objects pictured. Within each set of stimuli, a complete (C), an intermediate (I), and a most incomplete (MI) representation of the objects was constructed. In the first experiment, 60 subjects of three different age groups were tested on the MI representations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…The nursery school children identi- This analysis also revealed a significant effect of distinctive features [F(3 ,80) The results of this study extend and support previous results reported in this area (Gollin, 1960(Gollin, , 1961(Gollin, , 1962Murray & Szymczyk, 1978). These studies also reported differences in recognitions of incomplete pictures between children and adults.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The nursery school children identi- This analysis also revealed a significant effect of distinctive features [F(3 ,80) The results of this study extend and support previous results reported in this area (Gollin, 1960(Gollin, , 1961(Gollin, , 1962Murray & Szymczyk, 1978). These studies also reported differences in recognitions of incomplete pictures between children and adults.…”
Section: Resultssupporting
confidence: 82%
“…The present study was similar to Murray and Szymczyk's (1978) study , but included three degrees of fragmentation and four degrees of distinctive features for each pictorial representation. In this way, a more detailed analysis of the effects of fragmentations and distinctive features on perceptual recognition by children and adults could be obtained .…”
mentioning
confidence: 98%
See 3 more Smart Citations